A development of the Philippine Tables for LC Class H - Rosali, Rosemarie G. (Institute of Library Science, University of the Philippines Diliman, 1983)
This special problem is an expansion of the Library of Congress Class H for the Philippines based on the latest LC Class H schedules. It covers the Social Sciences (H) ; Statistics (HA) ; Economics (HB, HC , HD, HE, HF, HG, HJ) ; Sociology (HM) ; Social History and Conditions, Social Problems, Social Reform (HN) ; Family, Marriage, Woman (HQ) ; Associations, Societies, Clubs (HS) ; Communities, Classes, Races (HT) ; Social Pathology, Social and Public Welfare, Criminology (HV) ; and Socialism, Communism, Anarchism (HX).